Eating Cars: Food Citizenship in a “Community in Crisis” - Phillips, Lynne (Environnement urbain / Urban Environment)

(untitled) (Réseau Villes Régions Monde, 2012)
Guptill and Wilkins (2002) employ the concept of “food citizenship” to argue that engaging people more fully in decision-making about their own food systems encourages alliances between food producers and eaters and helps to build sustainable food environments. In this article my focus is on the development of community food citizenship, a phrase I use to draw attention to the dynamics of including all residents in the creation of new food systems. Focusing on a community’s diversity – to include, for example, residents who are economically marginalized and those who are economically privileged, as well as residents who are food activists and those who are not – highlights the pedagogical dimensions of initiating and building food citizenship in particular places. To sketch out some of the tensions in and possibilities for community food citizenship, I focus here on the case of Windsor, Ontario, a once thriving automotive centre now facing high unemployment rates and economic hardship. My relationship to this particular case study is as a participant in community efforts to develop an alternative food system and as a researcher/educator who is currently studying this process.